A FUNCTION PROPERTY OF POLYTROPHIC PROCESS WITH ASPECT OF TANGENT CONSTRUCTION - Pejović, B.; Mićić, V.; Perušić, M.; Tadić, G.; Smiljanić, S. (Journal of Engineering & Processing Management, 2009)
In this paper, starting from general tangent equation in arbitrary point of specified curve, using principles of differential geometry and given mathematical transformation tangent equation of polytrophic function in p – v diagram was obtained. This form is convenient for solving numerous practical and theoretical problems in engineering thermodynamic by means of graphical method. It was shown that tangent can be constructed easily, using polytrophic equation only, but it is not example with other functions appearing in thermodynamics. Later, in this paper, we have given some methods, which refer to more exact construction of polytrophic and graphical analyze of polytrophic process.